ANCAMAN BAHAYA LETUSAN GUNUNG API SKALA BESAR DAN MONOGENESIS DI INDONESIA - Bronto, S.; Setianegara, R. (Jurnal Geologi dan Sumberdaya Mineral, 2011)
Indonesia has a lot of volcanoes which their potentially hazards threaten people and environment. Mitigation efforts have been conducting to 129 active volcanoes where source locations and types of hazard are relatively well defined, mainly based on historical records. However, volcanic hazards due to larger eruptions, such as caldera explosions and gigantic volcanic debris avalanches, still require basic geological data. This also includes potentially hazard studies on monogenetic volcanoes, that may form a new vent at outside of the present active volcano. This idea is proposed based on facts that there has no a large scale explosion since the Tambora 1815 and Krakatau 1883 eruptions, but large scale tectonic activities have frequently occurred recently causing big tsunamis and earthquakes. Secondly, Sidoarjo mud volcano has been erupting for long time, and volcanic areas are occupied for living and business, intensively.Key words: hazard, volcano, caldera, explosion, avalanche, monogenetic